2018
DOI: 10.1021/acs.biochem.8b00186
|View full text |Cite
|
Sign up to set email alerts
|

Insights into the Active Site of Coproheme Decarboxylase from Listeria monocytogenes

Abstract: Coproheme decarboxylases (ChdC) catalyze the hydrogen peroxide-mediated conversion of coproheme to heme b. This work compares the structure and function of wild-type (WT) coproheme decarboxylase from Listeria monocytogenes and its M149A, Q187A, and M149A/Q187A mutants. The UV–vis, resonance Raman, and electron paramagnetic resonance spectroscopies clearly show that the ferric form of the WT protein is a pentacoordinate quantum mechanically mixed-spin state, which is very unusual in biological systems. Exchange… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
48
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 28 publications
(50 citation statements)
references
References 51 publications
(177 reference statements)
2
48
0
Order By: Relevance
“…Therefore, we concluded that in the A 1 conformation Q187 is H-bonded to bound carbon monoxide, as previously observed in SaChdC [9]. Interestingly, the open form (A 0 ) has also been observed in all CO adducts of the heme b products (containing two vinyl substituents in positions 2 and 4) of Lm ChdC [7]. These data indicate that in the coproheme complex, the interaction between the M149 residue and the propionate in position 2 has an important role in keeping glutamine 187 correctly positioned for the closure of the distal cavity and for the radicalic decarboxylation mediated by Y147.…”
Section: Introductionsupporting
confidence: 79%
See 4 more Smart Citations
“…Therefore, we concluded that in the A 1 conformation Q187 is H-bonded to bound carbon monoxide, as previously observed in SaChdC [9]. Interestingly, the open form (A 0 ) has also been observed in all CO adducts of the heme b products (containing two vinyl substituents in positions 2 and 4) of Lm ChdC [7]. These data indicate that in the coproheme complex, the interaction between the M149 residue and the propionate in position 2 has an important role in keeping glutamine 187 correctly positioned for the closure of the distal cavity and for the radicalic decarboxylation mediated by Y147.…”
Section: Introductionsupporting
confidence: 79%
“…Site-directed mutagenesis to obtain LmChdC M149A, Q187A and M149A/Q187A variants using the QuikChange Lightning Kit (Agilent Technologies) was described previously [7]. Generation of LmChdC Y147A, R133A, R179A, K151A, Y113A and Y113A/K151A, Y147A/R220A/S225A variants were produced following the same protocol with the primers listed in Table S1.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations